2016
DOI: 10.3389/fmicb.2016.00972
|View full text |Cite
|
Sign up to set email alerts
|

Serratia Secondary Metabolite Prodigiosin Inhibits Pseudomonas aeruginosa Biofilm Development by Producing Reactive Oxygen Species that Damage Biological Molecules

Abstract: Prodigiosin is a heterocyclic bacterial secondary metabolite belonging to the class of tripyrrole compounds, synthesized by various types of bacteria including Serratia species. Prodigiosin has been the subject of intense research over the last decade for its ability to induce apoptosis in several cancer cell lines. Reports suggest that prodigiosin promotes oxidative damage to double-stranded DNA (dsDNA) in the presence of copper ions and consequently leads to inhibition of cell-cycle progression and cell deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 59 publications
(73 reference statements)
0
36
0
2
Order By: Relevance
“…The biological role of these pigments in the producer organisms remains unclear. Bacterial PGs and their synthetic derivatives have antimicrobial (bactericidal and bacteriostatic) [ 109 , 110 , 111 , 112 ], antimalarial [ 109 , 110 , 113 ], and antitumor [ 109 , 110 , 114 , 115 , 116 ] activities. In addition, they have been shown to be effective apoptotic agents against various cancer cell lines [ 117 ], with multiple cellular targets including multi-drug resistant cells with little or no toxicity towards normal cell lines and induce apoptosis in T and B lymphocytes [ 118 , 119 ].…”
Section: Underlying Mechanisms Of Natural Compound-induced Autophamentioning
confidence: 99%
“…The biological role of these pigments in the producer organisms remains unclear. Bacterial PGs and their synthetic derivatives have antimicrobial (bactericidal and bacteriostatic) [ 109 , 110 , 111 , 112 ], antimalarial [ 109 , 110 , 113 ], and antitumor [ 109 , 110 , 114 , 115 , 116 ] activities. In addition, they have been shown to be effective apoptotic agents against various cancer cell lines [ 117 ], with multiple cellular targets including multi-drug resistant cells with little or no toxicity towards normal cell lines and induce apoptosis in T and B lymphocytes [ 118 , 119 ].…”
Section: Underlying Mechanisms Of Natural Compound-induced Autophamentioning
confidence: 99%
“…Prodigiosin (PG, PubChem CID: 5351169) is a red prodiginine pigment isolated from various bacteria including Serratia marcescens, Pseudoalteromonas rubra, Hahella chejuensis, and actinomycete bacteria [ 22 , 23 , 24 , 25 ]. Even though the original biological function in producer bacteria remains unclear, PG has been identified with numerous biological activities including antimicrobial [ 26 , 27 , 28 , 29 ], antimalarial [ 26 , 27 , 30 ], and antitumor [ 26 , 27 , 31 , 32 , 33 , 34 ] activities. Moreover, PG showed apoptotic inducing property in many cancer types such as lung cancer [ 35 , 36 , 37 ], breast cancer [ 38 , 39 ], colorectal cancer [ 40 , 41 , 42 ], leukemia [ 43 , 44 ], and hepatocellular carcinoma [ 45 ] without normal cell cytotoxicity [ 41 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Kimyon et al showed that prodigiosin (a heterocyclic bacterial secondary metabolite secreted by Serratia sp.) induces biofilm disruption and exhibits bactericidal activity against P. aeruginosa [98]. Prodigiosin-mediated P. aeruginosa biofilm disruption occurs by the release of H 2 O 2 and generation of hydroxyl radicals in the presence of copper ions that consequently cleaves/damages eDNA and alters P. aeruginosa cell surface hydrophobicity.…”
Section: Development Of New Antibacterial Agentsmentioning
confidence: 99%
“…Prodigiosin-mediated P. aeruginosa biofilm disruption occurs by the release of H 2 O 2 and generation of hydroxyl radicals in the presence of copper ions that consequently cleaves/damages eDNA and alters P. aeruginosa cell surface hydrophobicity. Prodigiosin also induces bacterial cell lysis as a consequence of the oxidative stress generated by H 2 O 2 [98].…”
Section: Development Of New Antibacterial Agentsmentioning
confidence: 99%